Other birds [large type] - Allen, Sarah Addison (Center Point Large Print, 2022)
"Down a narrow alley in the small coastal town of Mallow Island, South Carolina, lies a stunning cobblestone building comprised of five apartments. It's called The Dellawisp and it is named after the tiny turquoise birds who inhabit the building, alongside the human tenants, and imbue it with an air of magical secrecy. When Zoey Hennessey comes to claim her deceased mother's apartment at The Dellawisp, she meets her quirky, enigmatic neighbors, including a girl on the run, a grieving chef whose comfort food does not comfort him, two estranged middle-aged sisters, and three ghosts. Each with their own story. Each with their own longings. Each whose ending isn't yet written. When one of her new neighbors dies under odd circumstances the night Zoey arrives, she is thrust into the mystery of The Dellawisp. She soon discovers that many unfinished stories permeate the place, and the people around her are in as much need of healing from wrongs of the past as she is. To find their way they have to learn how to trust each other, confront their deepest fears, and let go of what haunts them." -- Provided by publisher.